Streamer parameters and breakdown in CO2. (24th November 2016) - Seeger, M; Avaheden, J; Pancheshnyi, S; Votteler, T
Abstract: CO2 is a promising gas for the replacement of SF6 in high-voltage transmission and distribution networks due to its lower environmental impact. The insulation properties of CO2 are, therefore, of great interest. For this, the properties of streamers are important, since they determine the initial discharge propagation and possibly the transition to a leader. The present experimental investigation addresses the streamer inception and propagation at ambient temperature in the pressure range 0.05–0.5 MPa at both polarities. Streamer parameters, namely the stability field, radius and velocity, were deduced in uniform and in strongly non-uniform background fields. The measured breakdown fields can then be understood by streamer propagation and streamer-to-leader transition.